2017
DOI: 10.2337/db16-1023
|View full text |Cite
|
Sign up to set email alerts
|

UBASH3A Mediates Risk for Type 1 Diabetes Through Inhibition of T-Cell Receptor–Induced NF-κB Signaling

Abstract: Although over 40 type 1 diabetes (T1D) risk loci have been mapped in humans, the causative genes and variants for T1D are largely unknown. Here, we investigated a candidate gene in the 21q22.3 risk locus—UBASH3A, which is primarily expressed in T cells where it is thought to play a largely redundant role. Genetic variants in UBASH3A have been shown to be associated with several autoimmune diseases in addition to T1D. However, the molecular mechanism underlying these genetic associations is unresolved. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 40 publications
7
91
0
Order By: Relevance
“…The UBASH3A gene, also on chromosome 21, has been associated (and the association replicated) with T1D and has a role in the regulation of T cells (34). UBASH3A downregulates T-cell receptor-induced NFкB signaling (35). NFкB signaling regulates multiple aspects of the innate and adaptive immune system including the expression of IL2 (36), a pleiotropic cytokine whose roles include the regulation of self-tolerance (37).…”
Section: Discussionmentioning
confidence: 99%
“…The UBASH3A gene, also on chromosome 21, has been associated (and the association replicated) with T1D and has a role in the regulation of T cells (34). UBASH3A downregulates T-cell receptor-induced NFкB signaling (35). NFкB signaling regulates multiple aspects of the innate and adaptive immune system including the expression of IL2 (36), a pleiotropic cytokine whose roles include the regulation of self-tolerance (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, few GWAS regions in autoimmune diseases have yet converged on a causal gene. An exception is UBASH3A, encoding ubiquitin-associated and SH3 domain containing protein A, which functions as a negative regulator of NF-kB signaling in T cells on stimulation of the antigen T cell receptor (36). Noncoding susceptibility alleles within UBASH3A are associated with several autoimmune diseases, including type 1 diabetes and RA, and are also associated with increased transcription, thereby leading to reduced transcription of interleukin-2 (IL2) in effector T cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…An exception is UBASH3A, encoding ubiquitin-associated and SH3 domain containing protein A, which functions as a negative regulator of NF-kB signaling in T cells on stimulation of the antigen T cell receptor (36). Noncoding susceptibility alleles within UBASH3A are associated with several autoimmune diseases, including type 1 diabetes and RA, and are also associated with increased transcription, thereby leading to reduced transcription of interleukin-2 (IL2) in effector T cells (36). An association study by Liu et al identified one SNP (rs1893592) in UBASH3A that was significantly related to DAS28, CRP level and bone erosion in RA patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…It can be activated by multiple extracellular stimulations. In addition, it can participate in gene regulation under apoptosis and inflammation (22). Meanwhile, it has important physiological and pathological actions (23).…”
Section: Discussionmentioning
confidence: 99%